ANALYSIS OF FACTORS AFFECTING THE AVAILABILITY OF INPATIENT BEDS AT MITRA MEDIKA AMPLAS HOSPITAL - Hasibuan, Abdurahman Hanafi; Fitriani, Arifah Devi; Sudiro, Sudiro (HEARTY, 2026)
The availability of inpatient beds is a critical issue in healthcare systems that affects the quality and efficiency of hospital services. This study aims to analyze the factors contributing to the imbalance between the demand for inpatient care and bed capacity, as well as to evaluate the role of discharge management and room allocation systems at Mitra Medika Amplas General Hospital. A descriptive qualitative approach with a phenomenological design was employed. Data were collected through observation, documentation, and in-depth interviews with hospital management, healthcare providers, and patients, and analyzed thematically based on Patient Flow, Bed Utilization, and Supply–Demand theories. The findings indicate that limited inpatient bed availability is not solely caused by physical constraints such as the number of beds, but also by suboptimal discharge management and the lack of integration with hospital information systems. Hospital performance indicators show a Bed Occupancy Rate (BOR) of 105–121%, exceeding the ideal standard of 60–85%, with an Average Length of Stay (ALOS) of 4–5 days and a Turnover Interval (TOI) of 1 day. Despite relatively fast bed turnover, the high BOR reflects excessive pressure on service capacity, primarily due to delayed discharges, ineffective inter-unit coordination, and inconsistent implementation of early discharge policies. These conditions contribute to increased waiting times in the Emergency Department and decreased patient satisfaction and safety. This study recommends strengthening digital-based discharge management, implementing real-time bed monitoring systems, enhancing inter-unit coordination through multidisciplinary discharge teams, and adopting continuous quality improvement (CQI) strategies. The findings highlight the importance of integrating operational efficiency with service quality in hospital capacity management.